This I believe : [compact disc, unabridged] : the personal philosophies of remarkable men and women. - Allison, Jay; Gediman, Dan; Gregory, John, 1964-; Merrick, Viki; McCain, John, 1936-2018; Allende, Isabel; Buckley, William F., Jr., 1925-2008; Sheehan, Jason; Murrow, Edward R.; Powell, Colin L.; Keller, Helen, 1880-1968; Steinem, Gloria; et al. (Audio Renaissance, 2006)
Based on the National Public Radio series of the same name, This I believe features eighty essayists... from the famous to the unknown... completing the thought that begins the book's title.